PERANAN VÄ€DA VIDYÄ€ DALAM MENINGKATKAN MUTU PENDIDIKAN DI PERGURUAN TINGGI (Perspektif Filsafat Hindu) - Suwantana, I Gede (Jurnal Penjaminan Mutu, 2016)
This article describes the role of VÄda-VidyÄ for students at universities to improve the quality of education, which is still considered to be very low in Indonesia. VÄda-VidyÄ is the science of discussion contained in the Nyaya Sutra for the sake of seeking the right knowledge. VÄda-VidyÄ displays various theories that metaphysical-ontologically provide an overview of the sixteen categories (padartha), namely the things that must be mastered in order to achieve liberation through a true knowledge. Efforts to reach the right knowledge in epistemic described through four pramana, namely pratyaksha, anumana, upamana and sabdha. From the fourth pramana, pratyaksha is the most important, where three others depend. With a qualitative descriptive method, this article attempts to enter all the problems faced by Indonesian students by Kemendikbud through analysis of epistemology of VÄda-VidyÄ. In principle, if VÄda-VidyÄ can be correctly understood and actualized into learning activities, the quality of education in Indonesia will be improved.